The Effect of Financial Instruments on Capital Market Growth in Nigeria - Jibril Mohammed (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2021)
This study investigates the effect of financial instruments on capital market growth in Nigeria, using government bonds and equity securities as proxies for financial instrument while market capitalization was use as proxy for capital market growth. The study adopts the ex-post-facto research design. Quarterly data used in the study were sourced from CBN annual statistical bulletin for relevant years (2012-2020). Descriptive statistics and the ordinary least square (OLS) multiple regression techniques were the main statistical tools used in the analysis of data. Additionally, the study conducted unit root test and test for cointegration to ascertain stationarity and long run relationship respectively. The modern portfolio theory was adopted for the study as it provides the most useful theoretical explanation for the study. The findings from the study, reveals that the combined outcome of the two explanatory variables used in this study have significant relationship with capital market growth. Based on the findings, the study concludes that financial instruments are a good predictor of capital functions in an economy by means of providing liquidity for both government and private investors. Therefore, the study recommends that financial instrument should be properly supervised and regulated as it forms an integral part of the capital market and serves important functions in an economy by means of providing liquidity for both government and private investors. Keywords: Financial Instrument, Market Capitalization, Bonds, Equity Securities